A case of Fournire’s Gangrene reconstructed by Anteriomedial Fasciocutaneous thigh Flap in Karnali Academy of Health Sciences, Jumla - Neupane, M; Devkota, H; Menyangbo, S; Paudel, S (Journal of Karnali Academy of Health Sciences, 2018)
Not available.